The Effects of employee perception of training effectiveness on organizational commitment: The moderating effects of organizational culture - Kim, Yejin; Kim, Jungsik (Korean Journal of Industrial and Organizational Psychology, 2020)
In order to cope with rapid changes in current business environment, the pursuit of competitive advantage through the optimal use of human capital is one of the most important strategies to the firms. The employee training plays a key role in cultivating human capital, which can not only bring higher organizational performance but also create strong corporate values. Considering the fact that unique organizational culture in each firm affects the attitudes of organizational members in various ways, we sought to explore the role of organizational culture in order to examine how employee perception of training effectiveness affects organizational commitment. For this purpose, this study tests the relationship between employee perception of training effectiveness and organizational commitment and moderating effects by two types of organizational cultures in this relationship. Based on the analyses of the HCCP data, the results of this study showed that the employee perception of training effectiveness has a significant positive relationship on organizational commitment and that the relationship is constant in the clan-oriented organizational culture, whereas it is significantly weakened under the market-oriented organizational culture.